2015
DOI: 10.1111/ijlh.12393
|View full text |Cite
|
Sign up to set email alerts
|

Detection of malignant cells in serous body fluids by counting high‐fluorescent cells on the Sysmex XN‐2000 hematology analyzer

Abstract: As serous body fluids will be more analyzed on automated analyzers in the future, HFC count can be a useful tool to select samples for microscopic review. Microscopic evaluation should be performed if HFC values are above a certain threshold (e.g. ≥17 HFC/μL) or in case of clinical suspicion of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
53
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(72 citation statements)
references
References 12 publications
12
53
3
4
Order By: Relevance
“…However, Cho et al (23) reported a cutoff of 6.9 cells/100 WBC, whereas Labaere et al (24) reported a cutoff of 17 cells/ 100 WBC. Two studies have recently been published about the sensitivity of the HF-BF cells ratio for the detection of tumor cells in serous fluids, but the results are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…However, Cho et al (23) reported a cutoff of 6.9 cells/100 WBC, whereas Labaere et al (24) reported a cutoff of 17 cells/ 100 WBC. Two studies have recently been published about the sensitivity of the HF-BF cells ratio for the detection of tumor cells in serous fluids, but the results are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off values of HFC% and HFC# were 4.4% and 24.5/μL, respectively, whereas the values for AUC and sensitivity and specificity were 0.707, 0.792, 0.558 and 0.708, 0.753, 0.550, respectively, which were slightly lower than what was reported in the literature. [6,7] During chronic inflammation, the number of mesothelial cells and macrophages were significantly increased in the effusion, and their nuclei contained more nucleic acids, which can be combined with more nucleic acid fluorescent dyes, and thus can be classified as high-fluorescent nucleated cells. In this experiment, we observed that liver cirrhosis ascites specimens contained many high-fluorescence nucleated cells, which were mainly classified as mesothelial cells and/or macrophages by microscopic examination Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The XN‐BF module uses fluorescent flow cytometry with hydrodynamic focusing for generating total count (and classification) of RBC, WBC (XN‐WBC‐BF), and TC (XN‐TC‐BF) in BF samples. Briefly, a total volume of 88 µL is used for each BF sample . In the BF‐mode, the combination of laser side scatter (SSC), forward scatter (FSC), and fluorescence analysis (SFL) allows classifying nucleated cells, which are clustered in the WDF‐scattergram according to their complexity ( x ‐axis), size ( z ‐axis), and nucleic acid content ( y ‐axis).…”
Section: Methodsmentioning
confidence: 99%
“…The cytometric assessment of BFs is typically performed in modern hemocytometers using a dedicated channel, conventionally known as BF mode (BF‐mode) . The presence of certain types of cells, usually absent in peripheral blood but occasionally identifiable in BFs (eg, macrophages, mesothelial cells, not hematological neoplastic cells, and synoviocytes), is perhaps the most important limitation of automated cell counting . All these cells share some common morphological features, including medium‐large size, biological activity (eg, replication or activation) and medium or high cytoplasmic complexity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation